O nekotoryh osobennostâh internet-pozdravlenij v različnyh kulʹturah - Lassan, Èleonora (Stylistyka, 2020)
Online greetings in Russian, Polish and German are analyzed in this article. The author treats greetings as a speech act that helps the addresser remind the addressee about his warm feelings towards him/her on the basis of a particular occasion - for instance, the birthday of the addressee. The author analyzes this speech act in relation to peculiarities of communicative and mental scenarios of the culture to which the speaker belongs. The entirety o f standard speech acts and the combination o f intentions of the speakers form a genre. The genre o f modem online greetings seems contiguous to folklore genres because most of the texts do not have authors. Moreover, these texts move from one Internet site to another. Therefore, there is a wide circle of ‘implementers’ - users. The author distinguishes some typical characteristics of online greetings in three cultures. The emphasis on the figurę o f the speaker and incantation character are typical to Russian greeting texts. Happmess, health and etemal youth are the key objects o f Russian greetin g texts Russian nreet gs are related to the futurę. German greetings are mainly related to the birthday celebration itself. Greetings are often related to the review of a life: it is wished that this day the addressee has madę surę that he/she has lived this year in the right way. Word courage (Mut) is constantly repeated in German greetings while this word is absent in Russian greetings. The figurę of the speaker is marginally expressed in Polish greetings. The sweetness of life is present in Polish greetings, whereas it is not observed in German and Russian texts. May all your dreams come true is a cliche element o f Polish greeting texts. The author relates detected specific features of online greetings with the ideas ot philosophers and historians on the peculiarities o f the expression of national character.